1981
DOI: 10.1126/science.7027441
|View full text |Cite
|
Sign up to set email alerts
|

Hemin Lyses Malaria Parasites

Abstract: Malaria parasites isolated from mouse erythrocytes are lysed by ferriprotoporphyrin IX chloride (hemin) or by a chloroquine-hemin complex in amounts that could be produced by release of less than 0.1 percent of the heme in erythrocytic hemoglobin. This effect of hemin may explain the protection against malaria provided by thalassemia and other conditions causing intracellular denaturation of hemoglobin. The toxicity of the chloroquine-hemin complex may explain the selective antimalarial action of chloroquine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
88
0

Year Published

1983
1983
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 194 publications
(90 citation statements)
references
References 14 publications
1
88
0
Order By: Relevance
“…Hb degradation, however, generates free heme and reactive oxygen species (ROS), the combination of which is highly deleterious to erythrocytic schizonts [22] as well as to the infected host.…”
Section: Deleterious Effects Of Free Hemementioning
confidence: 99%
See 1 more Smart Citation
“…Hb degradation, however, generates free heme and reactive oxygen species (ROS), the combination of which is highly deleterious to erythrocytic schizonts [22] as well as to the infected host.…”
Section: Deleterious Effects Of Free Hemementioning
confidence: 99%
“…Under homeostatic conditions, ferric HbFe 3+ (αβ) is scavenged by haptoglobin (Hp). The very high affinity of Hp towards Hb (>10 10 mol −1 in humans) is sustained by two Hp-binding sites in the Hb β chain, i.e., β [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25] and β 131-146 and one in the α chain, i.e., α 121-l27 [94]. Binding of Hp to Hb also stabilizes heme, inhibiting its release [95].…”
Section: Deleterious Effects Of Free Hemementioning
confidence: 99%
“…Hemin can cause lysis of mouse [1,2] and human erythrocytes [3] and of malaria parasites [4,5]. Other types of cells were demonstrably resistant to this lytic effect (see Ref.…”
Section: Introductionmentioning
confidence: 99%
“…Cohen et al first observed quinoline-heme complexes that were postulated to be toxic to the malaria parasites (7). Subsequent work demonstrated quinolone-heme complex interference with Plasmodium enzymes and insertion into membranes (8). However, this substrate hypothesis was not able to explain why many quinoline drugs that bind heme were unable to kill the malaria parasite.…”
mentioning
confidence: 99%